1991
DOI: 10.1002/eji.1830210529
|View full text |Cite
|
Sign up to set email alerts
|

T cell reactivity to an epitope of the mycobacterial 65‐kDa heat‐shock protein (hsp 65) corresponds with arthritis susceptibility in rats and is regulated by hsp 65‐specific cellular responses

Abstract: Adjuvant arthritis (AA) can be induced in genetically susceptible rats by immunization with heat-killed mycobacteria suspended in mineral oil. From our analysis of arthritogenic T cell clone A2b, obtained from an arthritic Lewis rat and specific for the 180-188 epitope of mycobacterial 65-kDa heat-shock protein (hsp 65), the possible origin of AA was explained by the existence of a molecular mimicry of the 180-188 epitope with a cartilage-associated self antigen. We now have shown that Lewis rats respond to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…The disease cannot be induced in resistant strains of rats (e.g., Brown-Norway (BN), Fisher) (3,4), and Lewis rats develop resistance to reinduction of the disease after recovery from arthritis (5,6).…”
Section: A Djuvant Arthritis (Aa)mentioning
confidence: 99%
See 2 more Smart Citations
“…The disease cannot be induced in resistant strains of rats (e.g., Brown-Norway (BN), Fisher) (3,4), and Lewis rats develop resistance to reinduction of the disease after recovery from arthritis (5,6).…”
Section: A Djuvant Arthritis (Aa)mentioning
confidence: 99%
“…Preimmunization of susceptible rats with the mycobacterial HSP65 leads to resistance to induction of the disease by MT. This protective effect is believed to be mediated by T cells specific for HSP65 (3,7,17,18). Likewise, although arthritic rats develop vigorous T cell responses to self-HSP and to peptide 180 -188 of the MT HSP65, neither of these molecules is arthritogenic when administered to arthritis-susceptible rats (19,20).…”
Section: A Djuvant Arthritis (Aa)mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, however, depleting F344 rats in vivo of OX8 + cells did not make this strain susceptible to exacerbations [8]. In addition, Hogervorst et al [9] also found that in AA responsiveness to certain mycobacterial antigen epitopes could be related to susceptibility. However, in this study the nonresponsiveness of the F344 appeared not to be due to antigenspecific suppression.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which BCTD bring about these effects is currently under investigation. However, because the nature of microbial flora in different conventional facilities might be different, it is likely that T cell responses to certain Bhsp65 determinant regions (6,38,39) other than, or in addition to, BCTD might be crucial in inducing suppressive effect on AA in F344 rats. In addition, microbial agents can also influence susceptibility to autoimmunity by mechanisms other than determinant mimicry, e.g., bystander activation of potentially autoreactive T cells (34,40), and by the action of superantigen (41).…”
Section: Discussionmentioning
confidence: 99%